A novel media properties-based material removal rate model for magnetic field-assisted finishing. (June 2018) - Kum, Chun Wai; Sato, Takashi; Guo, Jiang; Liu, Kui; Butler, David
Highlights: A semi-empirical equation for material removal for magnetic finishing is proposed. Proposed equation is based on particle packing theory and contact mechanics. Maximum material removal is when abrasive-to-iron volume ratio is 0.259. Equation is validated experimentally for a two-magnet magnetic finishing process. Abstract: Magnetic field assisted finishing (MFAF) is a category of non-conventional finishing processes that use magnetic field to manipulate finishing media typically consisting of magnetic particles and non-magnetic abrasives suspended in a carrier fluid. In order to better control the process, an improved understanding of the actual removal process is needed. This paper introduces a new material removal rate model for magnetic field-assisted finishing (MFAF) that aims to do so. The model considers the complexity of finishing media used in MFAF processes, where two different types of particles are present and interact with each other. The proposed material removal rate expression is based on contact mechanics and is a function of number of active magnetic particles, number of active abrasives, force per magnetic particle, and force per abrasive. Expressions for particle numbers were developed by considering an ideal face-centred cubic configuration for the magnetic particle network, while expressions for forces were developed based on a proposed framework for the particle interactions. The model was verified experimentally for a double-magnet MFAF process by varying the abrasive size and abrasive concentration. When the abrasive size was increased from 0.6 μm to 15 μm, the material removal rate decreased, consistent with the theoretical trend given by the model. Then, when abrasive concentration, given by the abrasives-to-carbonyl-iron volumetric ratio, was increased from 0 to 0.768, the material removal rate initially increased and then reached a maximum when the volume ratio is 0.259 before decreasing with further increase of the volume ratio. This is also in agreement with the theoretical trend given by the model. Graphical abstract: